Occurrence of Leptospira spp. and factors associated with the infection in horses from a military contingent in the Rio Grande do Sul State, Brazil - Mariane Pacheco Bastiani; Luciane Teresinha Lovato; Ana Eucares von Laer; Luciana Pötter; Rogério Oliveira Rodrigues; Bianca Costabile de Souza; Geder Paulo Herrmann; Luis Antonio Sangioni; Sonia de Avila Botton (Brazilian Journal of Veterinary Research and Animal Science, 2021)
The seroprevalence of Leptospira spp. and infection risk factors were investigated in horses from a military contingent in the Rio Grande do Sul State, Brazil. A total of 446 horses were evaluated and categorized into 309 mares, 11 stallions, and 126 horses with an average age of three years. To determine seroprevalence, serum samples from all horses were submitted to the microscopic agglutination test against 12 serovars belonging to nine serogroups, usually circulating in equine populations. To investigate the possible risk factors of infection by Leptospira spp., questionnaires were applied in that military unit. The seroprevalence in the horses with an average age of 3 years, mares, and stallions were 57.94% (73/126), 54.05% (165/309), and 45.45% (5/11), respectively. The main risk factors identified were contact with different water sources, the presence of rodents, and contact with wild and domestic animals. The high seroprevalence of anti‑Leptospira spp. antibodies may be associated with the presence of these risk factors. Therefore, the exposure of horses to possible reservoirs of Leptospira spp. should be minimized. Also, the immunoprophylaxis protocol should be reviewed and a shorter interval between vaccinations adopted to control leptospirosis in this herd.